Verifiable special threshold secret sharing scheme based on eigenvalue - Yanshuo ZHANG; Wenjing LI; Lei CHEN; Wei BI; Tao YANG (Tongxin xuebao)
Utilizing the characteristic that the characteristic equation of the n-th order matrix have multiple roots,the secret distributor distributes two different sub-keys to each participant,and these two sub-keys satisfy two conditions:linear independent and equality of the corresponding characteristic values.In the process of sub-key distribution and master key recovery,the black box can judge the authenticity of the participants’ activities through the characteristics of the sub-keys.If the two sub-keys have satisfied two conditions of linear independence and equal feature values,it can be determined that the participant’s activity is honest,otherwise,it can be determined that there exists fraudulent activity.The analysis results show that the scheme is correct,secure,and the information rate is 12.